SEMIOTICS IN JOHN STEINBECKâ€™S â€œGRAPE OF WRATHâ€ - masofa, ima (Dinamika : Jurnal Sastra dan Budaya, 2017)
This article analyzes signs aspects of Steinbeckâ€™s The Grapes of Wrath by using the Pierceâ€™s concept of semiotics. This article analyzes the semiotic aspects of Steibeckâ€™s The Grapes of Wrath by using the Pierceâ€™s concept of symbolic that is symbol,iconic and index.Symbol in Steinbeckâ€™s the grapes of wrath is road. Iconic in Steinbeckâ€™s the Grapes of Wrath is music. Index in Steinbeckâ€™s the Grapes of Wrath is bank.Keywords: Symbol,Iconic,IndexÂ